The Association between Glucose Control and Functional Indices in Older People with Diabetes. (23rd December 2018) - Azmon, M.; Gayus, N.; Michal, H.; Olmer, L.; Cukierman-Yaffe, T.
Abstract : Diabetes may be viewed as a disease of accelerated aging as it is a risk factor for physical disability and impairment in simple and complex activities, and is a higher risk for falls and fractures. Data from the last several years suggests that this increased risk is due not only to recognized diabetes complications but also to an accelerated decline in physical capacity due to lower muscle quality and a more rapid decline in muscle mass and lower extremity strength over time. Aim . To find the association between glucose control and functional indices. Methods . A cross-sectional study conducted at the Center for Successful Aging with Diabetes at the Sheba Medical Center. Individuals with a diagnosis of type 2 diabetes over the age of 60 were included. Functional status was assessed using tools that assess aerobic, strength, and balance capacities. Medical assessment was conducted through interview, physical examination, and collection of information from medical records. The association between functional indices and A1C was assessed using linear regression. Results . 153 consecutive individuals were evaluated. There was an inverse association between A1C and score achieved on the 6-minute walk; with increasing meters walked on the 6-minute walk test, there was a reduction in A1C (p = 0.003 ). There was also an inverse association with the 10-meter walk (p = 0.007 ), BERG balance test (p = 0.0006 ), and timed up and go (p = 0.01 ). Conclusion . In this cohort of older people with diabetes, there was an association between A1C and measures of functional indices. Future studies of glucose-lowering medication should include physical and functional assessment.